Facing the enigma of the vascular network in hepatocellular carcinomas in cirrhotic and non-cirrhotic livers. Issue 2 (4th August 2015) - Vasuri, Francesco; Fittipaldi, Silvia; Giunchi, Francesca; Monica, Melissa; Ravaioli, Matteo; Degiovanni, Alessio; Bonora, Sonia; Golfieri, Rita; Bolondi, Luigi; Grigioni, Walter F; Pasquinelli, Gianandrea; D'Errico-Grigioni, Antonia
Abstract : Aims: In this paper we aimed to analyse the typology and the phenotype of the different vascular modifications in human hepatocellular carcinomas (HCCs) with a new immunomorphological and gene expression approach. We also attempted to correlate these modifications with the histological parameters of tumour aggressiveness and the surrounding liver parenchyma. Methods: Ninety-six HCCs (from 80 patients) were retrospectively enrolled, 46 occurring in non-cirrhotic livers, and 50 in livers transplanted for cirrhosis. Histopathological analysis, immunohistochemistry for CD34, Nestin and WT1 and RT-PCR for Nestin, transforming growth factor-β1 (TGFβ1) and insulin-like growth factor 1 (IGF1R) mRNA were performed in all nodules. Results: By correlating the CD34 and Nestin immunoreactivity in HCC vasculature with the tumorous architecture, we identified four vascular patterns (named from 'a' to 'd'). Each of them was characterised by different expressions of TGFβ1 and IGF1R mRNA. Pattern a showed CD34-positive/Nestin-negative sinusoids, and was prevalent in microtrabecular lesions. Pattern b showed similar morphology and architecture as pattern a, but with Nestin-positive sinusoids and a significant 'boost' in IGF1R and TGFβ1 mRNAs. In patterns c and d a progressive sinusoid loss and a gain of newly formed arterioles were seen. Notably, HCCs with pattern a arose more frequently in cirrhosis (p=0.024), and showed lower incidence of microvascular invasion (p=0.002) and infiltration (p=0.005) compared with HCCs with other patterns. Conclusions: Although future studies are surely required, the identification of different vascular profiles in HCCs from cirrhotic and non-cirrhotic livers may help clarify the relationship between HCC progression and aggressiveness.